An attitude of veterinary practitioners towards animal rights in Turkey - Ozen, A; Ozturk, R; Yasar, A; Armutak, A; Basagac, T; Ozgur, A; Yerlikaya, H (Czech Academy Agricultural Sciences, 2004)
The authors examined the attitudes of veterinary practitioners in Turkey towards animals' right to life. For this purpose, a telephone questionnaire was applied on a total of 303 practitioners located in four provinces in Turkey. The overall response rate was 82%. The respect for right to life was valued slightly over neutral. According to the 5-point Likert scale, the average value scored by the participants for the items of views about animals' right to life was found as 3.25. Type of practice (pet clinics: 3.41), gender (females: 3.63), perceived responsibility (to animal: 3.48), keeping a pet (yes: 3.34) and membership in a society (yes: 3.67) had a statistically significant influence on attitudes towards animals' right to life. Independent variables explained 87% of the variance in attitudes, with most of the variance accounted for by perceived responsibility.
Keywords: animal rights; animals' right to live; veterinarian; veterinary practitioners